(untitled) (Journal of Fatima Jinnah Medical University, 2018)
OBJECTIVES: To determine the mean values of different morphometric measurements from the both ears, head and neck in the study population and to explore the variations in their size. STUDY DESIGN: Cross sectional survey PLACE AND DURATION OF STUDY: This study was conducted in Department of ENT Unit 1, Mayo Hospital associated with King Edward Medical University, Lahore. MATERIAL AND METHOD: A total of 75male volunteers from 28 main cities of the Punjab, visiting ENT department of Mayo Hospital Lahore, were randomly selected and recruited for the study. Surface measurements were taken directly from the ears, head and neck of all the subjects included in the study, by inch tape and electronic digital caliper. Each variable was measured twice in centimeters by the same investigator. Demographic profile and relevant data was recorded in a standard proforma. Mean of different morphometric values of both ears and Head & Neck were taken. RESULTS: Average vertical, horizontal and circumferential length of right ear was 6.728 cm, 2.992 cm and 13.766 cm while of the left ear, it was 6.757 cm, 3.16 cm and 10.684 cm respectively. Average circumference of head and neck remained 55.59 cm and 32.257 cm respectively. Mean length of the neck (between mental protuberance and suprasternal notch) was 17.869 cm among all the volunteers. CONCLUSION: This study furnished the first set of metric data of auricular dimensions for normal Pakistani males between 14 to 63 years of age. It can be helpful to correct congenital malformations and external ear deformities and may be useful for hearing instruments industry and forensic applications